THE EFFECT OF TAX KNOWLEDGE AND MODERNIZATION OF THE TAX ADMINISTRATION SYSTEM ON INDIVIDUAL TAXPAYER COMPLIANCE - Lestari, Tri Yuli; Khasanah, Uswatun (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
This research aims to determine whether there is an effect of tax knowledge and modernization of the tax administration system on individual taxpayer compliance in Bahagia Village Babelan Bekasi West Java. The variable used in this research is tax knowledge and modernization of the tax administration system as the independent variable and individual taxpayer compliance as the dependent variable. The population used in this research is taxpayers in Bahagia Village Babelan Bekasi West Java. The sample selected in this research used a purposive sampling method with predetermined criteria. The sample used is 100 respondents””methods of data collection by using a questionnaire. The data analysis technique in this research used a research instrument test, classical assumption test, and multiple linear regression analysis. The results of this research indicate that partially and simultaneously, tax knowledge and modernization of the tax administration system have a positive and significant effect on individual taxpayer compliance.